THE EXPLANATION OF THE ISSUES OF FREEDOM AND LONELINESS IN THE PHILOSOPHY OF JEAN-PAUL SARTRE (Modern American Journal of Social Sciences and Humanities, 2026)
When discussing the features of existential anthropology, an important place is occupied by the issues of human freedom and loneliness in the existential philosophy of Jean-Paul Sartre. According to him, man himself determines his existence and has no predetermined essence. Freedom occupies a central place in Sartre's philosophy: man himself shapes his life through his choices and actions. At the same time, this freedom leads to loneliness, since each person must make decisions independently. The article analyzes the thoughts of J.P. Sartre on this matter.